Educating city: ecosystem college career choice - Sosa Peinado, Eurídice (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2015)
It presents to itself the partial results of an exploratory investigation on the process of professional election of the young pre-university students in the Mexico City, where the dialogue was privileged on a) with whom, b) how and c) from what factors they choose for a professional option. Especially it is shared, some of the elements identified on behalf of the students who recount to what they learn inside and out of the school for the above mentioned election, which reveals us as the city itself and the interactions attend them and virtual in her for the pupils, they turn her into a stage and into an ecosystem of learning: like educational, regarding city without which it is not possible to think the election of his university education.